1998
DOI: 10.1007/bf02358433
|View full text |Cite
|
Sign up to set email alerts
|

The degree of starch phosphorylation as influenced by phosphate deprivation of potato (Solanum tuberosum L.) plants

Abstract: SummaryThe levels of starch phosphorylation in potato tubers were investigated in relation to fertilization with phosphorus (P) of field-grown and greenhouse-grown plants. The field-grown plants received 0, 15 or 30 kg P ha -1. Starch from plants grown without P-fertilizer contained 15.6 nmol P (mg starch) -l whereas starch from plants grown with 30 kg P ha -l contained 20.6 nmol P (mg starch) -1. The greenhouse-grown plants were cultured in inert media and received nutrient solutions containing 0, 3, 12 or 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 11 publications
1
14
0
1
Order By: Relevance
“…Most phosphorylation occurs at the C6 position (70–80%), while only 20–30% occurs at the C3 position . On average, one out of every 200–300 glucose units is reported to be phosphorylated . Noda et al studied the phosphorus content of 69 potato cultivars and reported a range between 434 and 1087 µg g −1 .…”
Section: Potato and Health: Compounds Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Most phosphorylation occurs at the C6 position (70–80%), while only 20–30% occurs at the C3 position . On average, one out of every 200–300 glucose units is reported to be phosphorylated . Noda et al studied the phosphorus content of 69 potato cultivars and reported a range between 434 and 1087 µg g −1 .…”
Section: Potato and Health: Compounds Of Interestmentioning
confidence: 99%
“…39 On average, one out of every 200-300 glucose units is reported to be phosphorylated. 40 Noda et al 41 studied the phosphorus content of 69 potato cultivars and reported a range between 434 and 1087 μg g −1 . The lowest content was observed in Setoyutaka and the highest in Kachikei No.…”
mentioning
confidence: 99%
“…Each pot contained five plants and 1 L of aerated nutrient solution. The nutrient solution used contained the following macro-and micronutrients: 1.8 mm KNO3, 0.2 mm MgSO4 · 7H2O, 0.7 mm NH4SO4, 1.25 mm Mg(NO3), 8.4 mm NaCl, 3.7 mm MnSO4, 1.6 mm ZnSO4, 0.76 mm CuSO4, 2.7 mm H3BO3, 0.18 mm Na2MoO4, 1.9 mm Ca(NO3)2 and 8 mm Fe-ethylenediaminetetraacetic acid (EDTA); the pH of the solution was adjusted to 5.5 (after Jacobsen et al 1998;Müller et al 2004). The plants were grown for 2 weeks with half strength of the nutrient solution supplied with 20 mm Pi (high-P plants) or 1 mm (low-P plants).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…The degree of phosphorylation has a profound effect on the physical and chemical properties of the starch. Because the degree of phosphorylation influences the qualitative properties of starch there is interest in the effect of environmental parameters; specifically, to what extent starch phosphorylation can be manipulated by controlling phosphate supply to the plants …”
Section: Introductionmentioning
confidence: 99%
“…Because the degree of phosphorylation influences the qualitative properties of starch there is interest in the effect of environmental parameters; specifically, to what extent starch phosphorylation can be manipulated by controlling phosphate supply to the plants. 12 Noda et al 13 studied the starch P content in potato cultivars and its effect on starch properties and their results indicated that enhancing the starch phosphate resulted in significant increases in the swelling power, peak viscosity, and breakdown and significant but small increases in the onset and peak temperatures of gelatinization. Other starch quality parameters, such as the amylose content, granule median size, and the gelatinization enthalpy, did not significantly change due to the degree of phosphate substitution of starch.…”
Section: Introductionmentioning
confidence: 99%